2023
DOI: 10.1039/d3fb00086a
|View full text |Cite
|
Sign up to set email alerts
|

Method for growing edibleEuglena gracilisin an inexpensive medium with tomato juice to a high cell density equivalent to the density in KH medium

Abstract: This paper proposes a low-cost technology for growing Euglena gracilis using beverages that people consume on a daily basis as a nutrient source. Among the 13 beverages tested, the most...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…C. reinhardtii is recognized for its industrial application as a nutritious food source [ 16 ], comparable to well-known microalgae like Euglena gracilis [ 17 , 18 ], Chlorella , and Spirulina . Notably, it surpasses these in starch and lipid content, earning FDA’s GRAS certification for its safety as a food additive [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. reinhardtii is recognized for its industrial application as a nutritious food source [ 16 ], comparable to well-known microalgae like Euglena gracilis [ 17 , 18 ], Chlorella , and Spirulina . Notably, it surpasses these in starch and lipid content, earning FDA’s GRAS certification for its safety as a food additive [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…C. reinhardtii is recognized for its industrial application as a nutritious food source [16], comparable to well-known microalgae like Euglena gracilis [17,18], Chlorella, and Spirulina.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to expand the industrial use of E. gracilis for food purposes, we have established a spectroscopic method for identifying carotenoids and hematochrome-like granules (structures resembling the eyespot but suggested not to contain carotenoids [ 29 ]) within single cells [ 30 ]. Additionally, we have developed an efficient cultivation method by growing it in foods, such as tomato juice beverages [ 31 ]. Building on these studies, we found that the carotenoid content in E. gracilis significantly increased when provided with nutrients from food (such as Katsuo dashi, a traditional Japanese fish stock) and an appropriate light environment (strong red light irradiation).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond these typical synthetic growth mediums, studies have been conducted using food and its by-products as substrates for the growth and upcycling of E. gracilis . These studies employed plant-based foods (tomato juice [ 31 ], spent tomato byproduct (STB) [ 35 ], potato liquor [ 36 ], corn steep solid [ 37 ], corn steep liquor and brewer’s spent grain [ 38 ], kinnow peel extract [ 39 ], tofu wastewater [ 40 ], and a mixture of sewage and organic wastes (molasses, corn steep liquor, and waste wine) [ 41 ]). Our research is the first to use an animal-based food (Katsuo dashi; Bonito stock) in this context.…”
Section: Introductionmentioning
confidence: 99%